2021
DOI: 10.3389/fimmu.2021.616650
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Characterization of Double Negative B Cells in the Blood of Individuals With Obesity

Abstract: We have previously shown that obesity is associated with increased secretion of IgG antibodies with anti-self-reactivity. In this paper, we confirm and extend our previous findings. We show that the plasma of individuals with obesity is enriched in autoimmune antibodies whose levels are positively associated with blood frequencies of the subset of Double Negative (DN) B cells, which is the most pro-inflammatory B cell subset. We also show that DN B cells, significantly increased in the blood of obese versus le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 62 publications
3
44
0
Order By: Relevance
“…Control ELISA plates were coated with BSA at a concentration of 10 µg/mL. MDA-specific optical density (OD) values were calculated by subtracting BSA OD values from MDA-BSA OD values [ 21 , 24 ].…”
Section: Materials/subjects and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Control ELISA plates were coated with BSA at a concentration of 10 µg/mL. MDA-specific optical density (OD) values were calculated by subtracting BSA OD values from MDA-BSA OD values [ 21 , 24 ].…”
Section: Materials/subjects and Methodsmentioning
confidence: 99%
“…Protein content was determined by Bradford [ 25 ]. AD at a concentration of 10 µg/mL were used to coat ELISA plates [ 21 , 24 ].…”
Section: Materials/subjects and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 18 , 20 , 21 Truth is that all these terms referred to B cell populations that share a number of features and are enriched in the peripheral blood of both elderly healthy individuals and people with chronic infectious diseases or inflammatory conditions, such as autoimmune disorders, obesity and cancer. 16 20 , 24 26 A recent study however, based on transcriptomic and IgH repertoire analyses of B cells, questions the equivalence of all these populations. 27 Here, we shall discuss the DN B cell population and its subsets, as well as the DN relationship to other B cells arising in autoimmunity and infections.…”
Section: The Population Of Double-negative (Dn) B Cellsmentioning
confidence: 99%
“…In this study, we have measured the presence of antibodies with autoimmune specificities in the sera of lean (BMI <25) and obese (BMI>30) COVID-19 patients, as compared to age-, gender- and BMI-matched uninfected controls, without previous history of autoimmunity. This study included uninfected controls since obesity per se is associated with the secretion of autoimmune antibodies, as previously demonstrated (28, 34, 35). It has been recently shown that the sera of adult COVID-19 patients contain antibodies with autoimmune specificities (36).…”
Section: Introductionmentioning
confidence: 99%